The cognitive behavioural treatment of irritable bowel syndrome: feasibility of a nurse delivered model of guided self-help - Dainty, Andrew David (2016)
Background: Irritable bowel syndrome is a medically unexplained phenomena relating to the lower gastrointestinal tract with symptoms such as altered bowel habit and abdominal pain. Patients experience poor quality of life and consume significant healthcare resources. Mechanisms for the delivery of evidence based psychological interventions for irritable bowel syndrome within the National Health Service are lacking and the feasibility of these interventions is poorly understood.